Karakteristik Pasien Ketoasidosis Diabetik Sebelum dan Saat Pandemi COVID-19 di RSUD Abdul Wahab Sjahranie Samarinda - Muhammad Wiryansyah; Yuliana Rahmah Retnaningrum (Faculty of Medicine Universitas Mataram, 2021)
Background: The Corona Virus Disease-19 (COVID-19) pandemic has put obstacles in management of diabetes mellitus (DM) thus making patients more susceptible to complications, including diabetic ketoacidosis (DKA). DKA cases during the pandemic have been reported to increase and could be precipitated by COVID-19. This study aims to determine the characteristics of DKA patients before and during pandemic at Regional Public Hospital Abdul Wahab Sjahranie Samarinda Methods: This study uses a descriptive observasional design with total sampling method. The variables studied were demography, clinical, laboratory examination, and type of infection. Result: 59 patients were met the criteria (17 during pandemic vs 42 before pandemic). Adult age group (58,82% & 71,43%), female (64,7% & 66,67%), and DM type 2 (58,82% & 71,43%) were dominant in both groups. During the pandemic, cases of severe DKA were relatively high (82,35% vs 76,19%). Mortality was relatively decreased (23,52% & 45,23%), but still higher than other studies. Blood glucose levels, HbA1c, HCO3-, pCO2, anion gap, and leukocytes were relatively higher before the pandemic. Even so, we found higher levels of pH, ketonuria, urea, and creatinine during the pandemic. Among both group, almost all patients had history of infection that precipitate DKA (94,11% & 92,85%) with sepsis as the most common type of infection. However, we not found that Severe Acute Respiratory Syndrome-Corona Virus-2 (SARS-CoV-2) infection triggers DKA in this study. Conclusion: The COVID-19 pandemic has an impact on clinical and outcome of DKA patients